data about reproduction of the oriental rat snake (Ptyas mucosus Linnaeus, 1758) in feeding condition at the Nghe An province - An, Ong Vinh; Huynh, Dang Huy; Kien, Tran; Quang, Hoang Xuan (Academia Journal of Biology, 2014)
The reproduction of Ptyas mucosus includes 4 main periods: copulation, gestation, oviposition and after oviposition. The mating season of Ptyas mucosus begins from April to October, mainly at the beginning of April, May, June and July. The mating time depends on the temperature and the humidity of the environment (23.92-32.51oC, 69.7-85.87%): in April (from 10 am to 3 pm), especially from 11 am to 3 pm; in May, the copulation occurs both in the morning and in the evening, especially from 7 am to 4 pm; in June, July and August, from 6 am to 8 am and 2 pm to 7 pm; Ptyas mucosus rarely copulates in September and October, mainly at the end of the morning and the beginning of the afternoon (from 9 am to 2 pm). The characteristics of the copulation of Ptyas mucosus consists of three stages: having a new joy, copulation and post-copulation. There are many complicated behaviors in the first stage: attracting the attention, making primary and secondary impression. The female Ptyas mucosus copulates many times in the oviposition season, there is not the group mating phenomenon like grass-snake. The gestation period of Ptyas mucosus lasts for about 53 days to 73 days. The oviposition season of Ptyas mucosus is from June to August every year, usually in June and July. Egg-laying occurs almost all the time of the day but mainly at night. Ptyas mucosus lays only once a year. The number of eggs is 6 to 15, formally from 8 to 12. Eggs have well proportioned oval shapes, especially, some have pointed tips. Eggs are enveloped by hard shells. At first, eggs are soft, pinky-white, then, becoming ivory-white. Size and weight of eggs: 43.5-67.63 mm ´ 25.4-37.75 mm, 22.05-31.85 g. Ptyas mucosus don’t have characteristics of incubation. They protect their eggs in a short time (2-3 days), and then going away. The suitable temperature for incubation is 26.8-34.6oC, humidity 63-92%. Eggs hatch after 51-70 days. They cannot hatch at the higher temperatures of 35oC.